Distribution and Diversity of Macrobenthos in Sangu River, Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
This study was conducted to understand the macrobenthos distribution and abundance in Sangu River to monitor the aquatic pollution level. Both surface and sub-surface water and benthic sediments were collected from three stations of the Sangu River. A few indices viz. Shannon-wiener, Simpson, Margalef’s and Evenness were used to estimate the macrobenthic assemblages. In this study, a total of 11 major taxa comprising total 870 macobenthic species were identified. Shannon-wiener index was maximum (1.58) at lower part (LP) which indicated moderate to heavily pollute aquatic environment of the Sangu River. The average diversity values of Shannon, Evenness, Simpson and Margalef’s indices were 0.97, 0.43, 0.39 and 1.54 respectively. The concentration of dissolved oxygen was the lowest (4.90 mg/L) at LP and the highest (5.08 mg/L) at upper part (UP). This study showed that macrobenthos abundances was influenced by higher temperature, salinity, and pH. The percentage of organic carbon content was maximum (98.18%) at LP where the macrobenthic abundance was 330 individuals/m2, whereas it was minimum (80.77%) at UP where macrobenthic abundance was 248 individuals/m2 that indicated carbon content also influence the assemblages of the macrobenthos in the Sangu River. A clear gradient of physico-chemical and benthic soil parameters fluctuation was also found to be responsible for the variations of macrobenthos assemblage in the Sangu River.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(2), 2020, P 27-34